MR Imaging Appearance of Frontal Sinus Barotrauma - Segev, Yoram; Landsberg, Roee; Fliss, Dan M. (American Journal of Neuroradiology, 2003)
Summary: We present the case of a flight passenger who experienced acute and severe headache during landing. MR imaging was performed because the patient had a history of vascular malformation and revealed an incidental venous angioma. A mass lesion in the frontal sinus, consistent with submucosal hematoma secondary to barotrauma, was thought to be the cause of the headache. To our knowledge, this is the first case of sinus barotrauma described in the radiologic literature and the first to describe the associated MR imaging findings.